Performance evaluation of MEMS piezoelectric inertial energy generator - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Othman, Raihan; Salleh, Hanim (2011)
Vibration based inertial energy generators have become significantly popular due to the growing demand of wireless sensor networks which need miniature, portable, long lasting and easily recharged sources of power. Usage of hazardous batteries is an unacceptable solution to power up the densely populated nodes due to their bulky sizes and high battery replacement cost. As such, the viability of ‘green’ microelectromechanical (MEMS) vibration based inertial energy generator has become even more dominant. This paper reports the design and simulation of a cantilever piezoelectric inertial energy generator based on bulk silicon micromachining for wireless condition monitoring in power plants. Power plants generate ambient vibrations in the low kHz range which can be harvested to power the wireless condition monitoring circuits. Output power of the system will be enhanced when it is operated at the ambient resonance frequency. This paper discusses the effect of various lengths, shapes and volume of the cantilever beam, to its natural resonant frequency. The effect of different piezoelectric material with the maximum output power produced is also highlighted. The design and finite element modeling was conducted using MEM PZE module in Coventorware. TM